Ginący świat – "Lasy deszczowe" z cyklu "Ekomuzyka" Grażyny Pstrokońskiej-Nawratil - Bartos, Katarzyna (Res Facta Nova, 2021)
Lasy deszczowe [Rainforests] is, as Grażyna Pstrokońska-Nawratil said, “an attempt to capture the endangered beauty, stop the increasingly rushing time, it is a symbolic and personal work”. The piece came into being in 2013. The inspiration for the structure of this composition was ancient tragedy. In the case of Lasy deszczowe, the main characters, whose fate was sealed, are elements of nature – trees, humming birds and river. The composer wanted to depict one day from a rainforest’s life – from the time before daybreak till twilight. This article will discuss the genesis of the composition, musical and nonmusical media of programmacity, as well as narration in this concerto.